Association between Antenatal Care Utilization and Maternal Anemia in Pregnant Women: A Cross-sectional study in RMU & Allied Hospitals - Muhammad Ahmad Khalid, Muhammad Saad Khan, Rameen Khalid, Muhammad Mushahid Ullah, Humaira Bilqis, Muhammad Ali Riaz, Muhammad Hamza Sohail (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Antenatal care (ANC) is important for preventing maternal complications and improving health outcomes. In Pakistan, although many women contact ANC, there are still significant issues with timing, quality, and fairness in access. Objectives: This study looks at the relationship between ANC use and maternal complication of anemia, at RMU & Allied Hospitals. Materials and Methods: We carried out a retrospective cross-sectional study using hospital records of 385 women who were admitted for delivery between January 2024 and March 2025. We gathered data on sociodemographic, ANC details, maternal complications, and delivery outcomes. We used R software for statistical analyses, applying chi-square, Fisher’s exact, and Wilcoxon rank sum tests to find significant associations. Results: Anemia was present in 15.3% of the participants. It was notably more common among women from rural areas (22.1%), those with low education (27.9% among those with only primary education), and those from low-income backgrounds (17.1%) (all p < 0.05). Even though 98.06% of women had at least one ANC visit, those who started care later (after three weeks) and had more visits (a median of 6 for anemic women compared to 4 for non-anemic women, p = 0.010) were paradoxically linked to anemia, suggesting that they sought care after complications developed. Anemic women were more likely to arrive in poor condition, be in advanced labor, and have complications such as bleeding after 28 weeks and threatened miscarriage. Conclusion: Inadequate and delayed ANC was strongly tied to negative maternal outcomes, particularly anemia. Factors like living in rural areas, low education, and poverty increased the risks. These findings stress the need for early, fair, and effective antenatal care to enhance maternal health in Pakistan. Keywords: Antenatal care, anemia, Pregnancy complications, Healthcare Disparities, Pakistan, Rural health